1996
DOI: 10.1002/(sici)1097-0215(19961115)68:4<452::aid-ijc9>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral platinum concentrations in patients treated with repeated low‐dose cisplatin as a radiosensitizer

Abstract: The aim of the present study was to check whether platinum (Pt) concentrations achieved in tumors with a daily low-dose schedule were close to those promoting radiosensitization. Fifteen previously untreated patients with histologically proven advanced uterine cervix tumors were studied. They received a daily irradiation 30 min after a short infusion of 5 mg cisplatin for 5 consecutive days every week. A biopsy was taken from the accessible tumor mass, 4 to 6 hr after the daily injection. Blood samples were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Most studies measured intratumoral platinum content instead of cisplatin-DNA adducts in HNSCC patients [24][25][26][27] or cervical cancer patients. [28][29][30] Gouyette et al reported on intratumoral platinum content in HNSCC patients after cisplatin administration IV or IA. 24 Platinum concentrations in biopsies taken after IA infusion were slightly increased relative to IV treatment, but not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies measured intratumoral platinum content instead of cisplatin-DNA adducts in HNSCC patients [24][25][26][27] or cervical cancer patients. [28][29][30] Gouyette et al reported on intratumoral platinum content in HNSCC patients after cisplatin administration IV or IA. 24 Platinum concentrations in biopsies taken after IA infusion were slightly increased relative to IV treatment, but not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…The precise biochemical mechanisms of the interaction with radiation remain a matter of debate [8], but most arguments point to an inhibition of repair of sublethal damage by cisplatin through DNA cross-linkage. Experimental data indicate a non-saturable dose-dependency and time-dependency, with a tumour half-life of 94.4 h [9].…”
Section: Discussionmentioning
confidence: 96%
“…platin dose of 5-6 mg/m 2 [10] and these lower daily doses have been associated with sub-radiosensitising tumour concentrations [9]. 3.…”
Section: No Clear Benefit Has Been Shown For a Lower Daily Cis-mentioning
confidence: 99%
“…The cisplatin is an effective DNA crosslinking agent and it has been suggested that low-dose cisplatin could make the tumor cell radiosensitive and inhibit DNA repair processes (Fu et al, 1988;Lagrange et al, 1996). The accumulation of p53 is a key event in cisplatin-associated chemotherapy .…”
Section: Discussionmentioning
confidence: 99%